Sufi Motifs in Mahmud Darwish’s Poetry or Mahmud Darwish as a sufi Poet - Jamal Assadi; Mahmud Naamneh (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
This article will address the mask of Farid Ed-Din Al-Attar as depicted in Mahmud Darwish ’s poetry, with the goal of studying the confluence of the sufi mask and intertextuality, as well as poetry and meta-poetry. To be more explicit, this study will look into a few issues: Why did Darwish wear the mask of Al-Attar? Was it a mere fondness of a powerful ancestor? Was it a protest against the grave spiritual and intellectual deficit as well as poverty that plague current Arab literature? Was Al-Attar simply used as a sufi mask, or as a signal of inter- textuality? Was Darwish attempting to pay homage to an ancient ancestor without whom he would be unable to survive in the present and lead a successful struggle? In other words, did Darwish aim to use Al-Attar’s heritage to restore Arab poetry and its revolutionary spirit? If so, is Al-Attar a revived sufi living among us to guide in person the battle for freedom and to promote the level of Arab literature? Or was Darwish given life by Al-Attar, the sufi saint?